TELAAH KITAB TAFASSERE BICARA UGINA SURAH ‘AMMA KARYA AGH. MUHAMMAD AS’AD SENGKANG - Adinda, Nur; Shofa, Ida Kurnia; Ghifari, Muhammad (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2023)
This article examines one of the tafsir books compiled by AGH. Muhammad As'ad, one of the Indonesian clerics who is influential in South Sulawesi. The book of tafsir is entitled Tafasere Bicara Ugina Surah ‘Amma. This tafsir is among the first tafsir written using Lontarak script and in Bugis language, so this tafsir book provides a new nuance in the history of the study of al-Qur'an tafsir in South Sulawesi. The book of tafsir was translated into Indonesian by AGH. As'ad students, Sjamsoeddin Singkang. The book Tafasere Tafasere Bicara Ugina Surah ‘Amma is classified as a book that has little exposure to the general public, so no research has been found that examines this book of tafsir. This research aims to examine the characteristics, background of interpretation, sources, methods and styles used by AGH. As'ad in interpreting the Koran. This type of research is library research using descriptive analysis methods. From this research it can be seen that the Bugis community was the main target for writing the book Tafasere Bicara Ugina Surah ‘Amma because the community's understanding there is still very limited and there are still many ritual practices that are not in accordance with Islamic teachings and beliefs. As for the source of AGH interpretation. As'ad uses the bi al-ray tafsir method. From a methodological aspect, this interpretation uses the ijmali method with simple interpretation. The breadth of explanation falls into the category of bayani interpretation. The targets and order of verses are interpreted using the maudhu'i verse method. The style of interpretation tends to be towards faith and divinity, making it fall into the category of interpretation of the i'tiqadi style. Artikel ini mengkaji salah satu kitab tafsir yang disusun oleh AGH. Muhammad As’ad, salah satu ulama Nusantara yang berpengaruh di Sulawesi Selatan. Kitab tafsirnya diberi judul Tafasere Bicara Ugina Surah Amma. Tafsir tersebut termasuk tafsir pertama yang ditulis menggunakan aksara Lontarak dan berbahasa Bugis sehingga kitab tafsir ini memberikan nuansa baru dalam sejarah kajian tafsir al-Qur’an di Sulawesi Selatan. Kitab tafsir diterjemahkan ke dalam Bahasa Indonesia oleh murid AGH. As’ad, Sjamsoeddin Singkang. Kitab Tafasere Bicara Ugina Surah Amma tergolong kitab yang kurang terekspos di masyarakat umum, sehingga belum ditemukan penelitian yang mengkaji kitab tafsir ini. Penelitian ini bertujuan untuk mengkaji karakteristik, latar belakang penafsiran, sumber, metode dan corak yang digunakan AGH. As’ad dalam menafsirkan al-Qur’an. Jenis penelitian ini adalah penelitian kepustakaan (library research) dengan menggunakan metode analisis deskriptif. Dari penelitian ini dapat diketahui bahwa masyarakat Bugis menjadi sasaran utama penulisan kitab Tafasere Bicara Ugina Surah ‘Amma karena pemahaman masyarakat di sana masih sangat terbatas dan masih terdapat banyak praktik ritual yang tidak sesuai dengan ajaran dan keyakinan Islam. Adapun mengenai sumber penafsiran AGH. As’ad menggunakan metode tafsir bi al-ray. Dari aspek metolodogi, tafsir ini menggunakan metode ijmali dengan penafsiran sederhana. Keluasan penjelasan masuk pada kategori tafsir bayani. Adapun sasaran dan tertib ayat yang ditafsirkan menggunakan metode maudhu’i ayat. Corak penafsiran cenderung mengarah ke arah keimanan dan ketuhanan menjadikannya termasuk kategori tafsir corak i’tiqadi.